TRACKING ECOLOGICAL ISSUES IN MUSIC: KOES PLUS' SONG "KOLAM SUSU" IN NATURAL SYMBOLS - Bagaskara, Akbar; Rokhani, Umilia; Molo, Benediktus; Pratama, Wahyu; Alanta Dewa, Daggo (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2025)
The purpose of this research is to trace ecological issues in music, especially the song Kolam susu popularized by the band Koes Plus in 1973. The research method used in this research is a qualitative type, in which the form of data is descriptive narrative. Data sources in the research were taken from scientific articles, books, and public space information (netnography). The validation technique applied in this research is the triangulation technique and for the theory of analyzing the meaning of the lyrics used is the semiotic theory of Ferdinand de Sassure. The results of this study found (1) ecological issues have also become a concern for many music artists in the world, (2) Kolam susu songs in general include the first generation of music that represents ecological issues in the case of Indonesia, the popularity of Kolam susu songs also certainly has a strong impact on the distribution of positive ecological messages massively and widely (3) the presence of ecological criticism expression format in song media will make social messages more easily accepted by the public.